Indigenous Fruit Trees in the Tropics: Domestication, Utilization and Commercialization 2007
DOI: 10.1079/9781845931100.0341
|View full text |Cite
|
Sign up to set email alerts
|

Germplasm supply, propagation and nursery management of miombo fruit trees.

Abstract: In this chapter, we review the state of knowledge about germplasm delivery and the propagation and nursery management of miombo fruit trees in Africa. The chapter will be limited to examples relevant to small-farm agroforestry systems in southern Africa as opposed to highly intensive monocultural orchard production systems. We discuss the factors involved in determining the most appropriate methods of propagation for particular species, and the associated constraints and limitations in scaling up the domestica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Indeed, top grafting produced double the number of leaves, primary branches and internodes and exhibited more main branch length and large branch diameter than budding. These results concur with those of Akinnifesi et al (2008) and Tchoundjeu et al (2010).…”
Section: Effect Of Grafting Technique On Selected Growth Parameters Isupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, top grafting produced double the number of leaves, primary branches and internodes and exhibited more main branch length and large branch diameter than budding. These results concur with those of Akinnifesi et al (2008) and Tchoundjeu et al (2010).…”
Section: Effect Of Grafting Technique On Selected Growth Parameters Isupporting
confidence: 93%
“…Budding showed no shoot in all clones compared to top grafting which recorded significant shoots during the first WAG. The lower shoot formation with the budding technique could be attributed to the low carbohydrate reserves (Akinnifesi et al, 2008; Tchoundjeu et al, 2010). During the second WAG, top grafting recorded significantly higher shoots than budding in clones C9, C14 and C16.…”
Section: Effect Of Grafting Technique On Selected Growth Parameters Imentioning
confidence: 99%
“…Vegetative propagation (grafting, budding and marcotting) has also been used to achieve early fruiting and tree dwarfing (Akinnifesi et al, 2008;. For example, grafted Uapaca kirkiana began to produce fruits after only 2-3 years, while those derived from seedlings took 12-15 years before fruiting (Akinnifesi et al, 2008;. Moreover, dwarfing produces trees that are smaller at harvest, thus facilitating fruit collection.…”
Section: Beyond Vegetative Propagation Of Indigenous Fruit Treesmentioning
confidence: 99%
“…According to Bhojwani and Razdan (1996), a shift from sexual to clonal reproduction allows for the faithful reproduction of individuals with superior features (traits) by eliminating the uncertainty in the transmission of favoured traits over reproductive cycles which is associated with sexual reproduction. Vegetative propagation (grafting, budding and marcotting) has also been used to achieve early fruiting and tree dwarfing (Akinnifesi et al, 2008;. For example, grafted Uapaca kirkiana began to produce fruits after only 2-3 years, while those derived from seedlings took 12-15 years before fruiting (Akinnifesi et al, 2008;.…”
Section: Beyond Vegetative Propagation Of Indigenous Fruit Treesmentioning
confidence: 99%
“…According to Akinnifesi et al (2008), they observed that the success of grafting for Uapaca kirkiana depends on the skill of the grafter, management practices used after grafting, and the technique used. In this study, the period of grafting and the non-compatibility of rootstock and graft could have caused the low success rate.…”
Section: Discussionmentioning
confidence: 99%